Heavy metal residues in milk and dairy products produced in Northern Cyprus - Dagcilar, Kamil; Gezer, Ceren (Mattioli 1885, 2021)
Background: The present study aimed to determine the heavy metal concentrations (As-75, Cd-111, Pb-208, Cu-65, Hg-200) in milk and dairy products produced in Northern Cyprus with a view to evaluating the daily metal intake and potential health risks. Method: The study was conducted in a total of 616 individuals between the ages of 18 and 65, and the average daily consumption of milk and dairy products, in addition to body weight, were determined. Heavy metal concentrations in raw milk (cow, sheep, goat) and the most commonly consumed packaged milk products (UHT milk, yogurt, halloumi, lor, kashar, and white cheese) were determined by inductively coupled plasma-mass spectrometry (ICP-MS). Samples were taken from each product in triplicate, resulting in the analysis of a total of 27 samples. For evaluation of the potential health risks, the Health Risk Index (HRI) and Total HRI (THRI) were calculated using the results of packaged dairy product consumption, daily intake of metal, and oral reference level (RfD) (HRI<1, THRI<1 safe limits). Moreover, heavy metal concentrations were compared with maximum permissible limits (MPL). Results: As residue was detected only in raw sheep's milk samples (0.33 +/- 0.58 mu g/kg). The average As, Cd, Pb, Cu, and Hg residues in packaged products were 4.55 +/- 6.19 (range: 0.00-25.00 mu g/kg), 14.44 +/- 20.65 (range: 0.00-58.00 mu g/kg), 6.83 +/- 19.03 (range: 0.00-81.00 mu g/kg), 237.38 +/- 215.22 (range: 0.00-738.00 mu g/kg), and 4.61 +/- 6.37 (range: 0.00-24.00 mu g/kg), respectively. In addition, the calculated HRI and THRI values were below 1. Conclusions: According to the HRI and THRI results, no possible health risks were determined with respect to consumption of the analyzed products. Cd residue was higher than the MPL in yogurt, halloumi, and UHT milk samples, while Pb residue was higher than the MPL in halloumi samples, and Cu residue was higher than the MPL in yogurt, halloumi, white cheese, kashar, and for samples. It is important to control all steps that may cause heavy metal contamination during the processing of milk.
Keywords: Milk consumption; heavy metals; public health nutrition; food safety; potential health risk